1993
DOI: 10.1038/bjc.1993.48
|View full text |Cite
|
Sign up to set email alerts
|

The human EGF receptor as a target for cancer therapy: six new rat mAbs against the receptor on the breast carcinoma MDA-MB 468

Abstract: (Santon et al., 1986;Ozanne et al., 1986;Velu et al., 1987; Difore et al., 1987;Harris et al., 1990). In addition, some of these tumours produce ligands for the receptor and it has been suggested that an autocrine mechanism is involved in progression of cancers of this type (Sporn & Roberts 1985;Imanishi et al., 1988;Nistar et al., 1988; Dernyck 1990;Tateishi et al., 1990;Yoshida et al., 1990; Morishige et al., 1991). Over-expression of the EGFR by tumour cells, compared to their normal counterparts, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 26 publications
2
60
1
Order By: Relevance
“…Indeed, we have found that culture supernatants of A43 1 cells effectively block the binding of all of the rat antibodies to the receptor for EGF (Modjtahedi et al, 1993). The success of treatment clearly depends on antigen density and the results obtained with the SKOV 3 xenografts suggest that too few receptors were present to permit effective immune destruction.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Indeed, we have found that culture supernatants of A43 1 cells effectively block the binding of all of the rat antibodies to the receptor for EGF (Modjtahedi et al, 1993). The success of treatment clearly depends on antigen density and the results obtained with the SKOV 3 xenografts suggest that too few receptors were present to permit effective immune destruction.…”
Section: Discussionmentioning
confidence: 86%
“…We have shown (Modjtahedi et al, 1993 see accompanying paper) that a number of rat antibodies raised against the external domain of the human receptor for EGF were potent inhibitors of the growth in vitro of tumour cells that overexpress this receptor. In this paper we demonstrate that three of these antibodies, ICR16 (IgG2a), ICR62 (IgG2b) and ICR64 (IgG1) were also very effective inhibitors of the growth in athymic mice of several tumours that overexpress the EGFR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our aim was to obtain a diverse population of antibodies that bound to distinct epitopes on the EGFR and which were of different isotype in order to select the best MAb or combination of MAbs for therapeutic and diagnostic use. Of these, the IgG2b MAb ICR62 was prominent in that it (a) effectively blocks the binding of EGF, TGF-ai, and HB-EGF to EGFR; (b) inhibits the growth of EGFR-overexpressing tumour cell lines in vitro (Modjtahedi et al, 1993a;; and (c) was the most effective antibody in our MAb library for eradicating such tumours in athymic mice (Modjtahedi et al, 1993b;Dean et al, 1994). We have also reported recently that antibodies to the EGFR that inhibit the growth of EGFR-overexpressing tumours do so by inducing terminal differentiation and that a further therapeutic effect may be obtained via immunological mechanisms with rat IgG2b MAbs such as ICR62 .…”
mentioning
confidence: 99%